2016
DOI: 10.4236/aim.2016.613089
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Z N Staining vs. Flurochrome Staining and Impact of Sample Processing on Diagnosis of Tuberculosis from Various Clinical Samples

Abstract: Background: Tuberculosis is a highly infectious disease and India has the highest burden with it. Diagnosis of tuberculosis in many countries is still dependent on microscopy. Although its sensitivity is low in comparison to culture and molecular methods, its sensitivity can still be improved by using fluorescence staining method and processing of samples by homogenization and concentration method. Material and methods: Samples were collected from all newly registered suspected cases of tuberculosis in tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…In the present study the statistical difference between case detection rates by the two stains was statistically significant (p value < 0.05) (Table 3). This was in concordance with studies done in India by Mistry Y, et al [18], Jain A, et al [12], Dagar V, et al [19] as well as abroad by Zailani SB, et al [20] and Zaib-un-Nisa, et al [21] where all of them reported a statistically significant difference between case detection by the two staining techniques.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study the statistical difference between case detection rates by the two stains was statistically significant (p value < 0.05) (Table 3). This was in concordance with studies done in India by Mistry Y, et al [18], Jain A, et al [12], Dagar V, et al [19] as well as abroad by Zailani SB, et al [20] and Zaib-un-Nisa, et al [21] where all of them reported a statistically significant difference between case detection by the two staining techniques.…”
Section: Discussionsupporting
confidence: 91%